A multilevel perspective on gender in classroom motivation and climate: Potential benefits of male teachers for boys? - Marsh, H; Martin, A; Cheng, J (2008)
Are boys better motivated by male than female teachers in high school math, science, and English classes, and can these differences be explained by classroom climate? Using a cross-classified multilevel model with 5 levels (school, teacher, class, student, subject), the authors found little or no support for this contention. In general (except in terms of anxiety and persistence), girls were better motivated than boys, and these differences tended to generalize over student age and school subject in classes taught by both male and female teachers. Student perceptions of classroom climate were more specific to the group of students within a particular class than to the teacher who taught the class and had moderate to large effects on the motivation of individual students. The surprisingly small amounts of variance explained in motivation by student gender and age, teacher gender, school subject, and their interactions support a gender invariance and similarities model but not theoretical predictions based on gender stereotype, gender intensification, and gender matching perspectives. © 2008 American Psychological Association.